Short‐time water immersion inhibits browning of fresh‐cut potato by enhancing antioxidant capability and tyrosine scavenging. Issue 11 (1st September 2019) - Gong, Ying; Wang, Qingguo; Ma, Su; Ma, Yurong; Meng, Qingchang; Zhang, Zigang; Shi, Jingying
Abstract: Water immersion treatment of potato slices with various time periods (0–30 min) was studied to find out the effect on the browning of fresh‐cut potato slices during long‐term storage (1–12 days) at 5°C. The results show that water immersion for 15 min significantly inhibit browning compared to other time periods of immersion treatment. Further studies show that the levels of superoxide dismutase (SOD), ascorbate peroxidase (APX), glutamic acid, and proline were increased by the 15‐min water immersion treatment, while hydrogen peroxide (H2 O2 ) and superoxide anion (O2 ˉ) were lowered; and all these compounds alleviated the oxidation pressure of potato slices. Chlorogenic acid, tyrosine, and tyrosinase activities were lower than those of the controls, which helped decrease the enzymatic browning levels of treated slices. Nevertheless, the browning inhibition has no observable correlation with either total phenols or the peroxidase (POD) activity. Practical applications: The research provides a simple anti‐browning method for fresh‐cut potatoes during long‐term storage thus maintaining quality and extending shelf life; and it reports new experimental results detailing the physiological reactions induced by the short‐time water immersion of fresh‐cut potatoes. The physiological studies may promote the understanding of the browning mechanism of fresh‐cut potatoes and provide clues to further efforts in seeking novel strategies for browning inhibition of fresh‐cut potatoes.